Is the titer of adipokinetic peptides in Leptinotarsa decemlineata fed on genetically modified potatoes increased by oxidative stress? - Kodrík, Dalibor; Krishnan, Natraj; Habustová, Oxana (Peptides, 2007)
The level of adipokinetic hormones (AKHs) (Peram-CAH-I and II) in the corpora cardiaca and the hemolymph of Leptinotarsa decemlineata enormously increases in the adults fed on genetically modified potatoes containing either GNA lectin or Cry 3Aa toxin concomitant with increased oxidative stress in gut tissues. A similar enhancement of the AKH titer is achieved when the adults are injected with paraquat that evokes oxidative stress. On the other hand, an injection of exogenous AKH reduces oxidative stress biomarkers in the hemolymph by reducing protein carbonyls and enhancing reduced glutathione levels. These facts indicate that there is a feedback regulation between an oxidative stressor action and the level of AKH in the insect body, and that AKHs might be involved in the activation of an antioxidant protection mechanism. These results are to our knowledge, the first evidence for the involvement of AKHs in oxidative stress mitigation, in addition to a plethora of other roles.
Keywords: brouci; Plant Lectins; oxidační stres; Mannose-Binding Lectins; paraquat; posttranslační úpravy proteinů; hemolymfa; hmyzí hormony; rostlinné lektiny; Protein Processing, Post-Translational; ELISA; Oligopeptides; kyselina pyrrolidonkarboxylová; Pyrrolidonecarboxylic Acid; Plants, Genetically Modified; Enzyme-Linked Immunosorbent Assay; Animals; zvířata; lektiny vázající mannosu; Coleoptera; Insect Hormones; geneticky modifikované rostliny; Bacterial Toxins; Paraquat; Hemolymph; Oxidative Stress; oligopeptidy; Solanum tuberosum; bakteriální toxiny